2017
DOI: 10.1016/j.nrl.2016.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Asociación de polimorfismos de diaminoxidasa e histamina N metiltransferasa con la presencia, discapacidad y severidad de migraña en un grupo de madres mexicanas de niños alérgicos

Abstract: We suggest a synergistic association between HNMT and DAO functional polymorphisms and migraine; this hypothesis must be further confirmed by larger studies. However, the characteristics and ethnic differences between analysed populations should be considered when interpreting the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The DAO SNP rs10156191, associated with decreased DAO enzyme activity, seemed to be more frequent in the migraine population. In the same vein, another study performed by Meza-Velázquez et al [20] also found that a mutant DAO SNP was significantly more frequent in a group of women with migraine than in the control group. Despite that published studies seem to indicate that DAO deficit could be one of the triggers for headaches, data about serum DAO activity levels in affected populations would be important to support this association.…”
Section: Discussionmentioning
confidence: 69%
“…The DAO SNP rs10156191, associated with decreased DAO enzyme activity, seemed to be more frequent in the migraine population. In the same vein, another study performed by Meza-Velázquez et al [20] also found that a mutant DAO SNP was significantly more frequent in a group of women with migraine than in the control group. Despite that published studies seem to indicate that DAO deficit could be one of the triggers for headaches, data about serum DAO activity levels in affected populations would be important to support this association.…”
Section: Discussionmentioning
confidence: 69%
“…This enzymatic deficit may have its origins in genetic mutations. Different polymorphisms of a single nucleotide in the gene that encodes this enzyme ( AOC1 on chromosome 7) have been associated with lower DAO activity [14,15,16]. The deficit may also be due to acquired causes such as inflammatory bowel diseases that block the secretion of DAO [1,3,12], or to the inhibitory action of drugs, some of them with a very widespread use (e.g., acetylcysteine, clavulanic acid, metoclopramide, verapamil) [1,17].…”
Section: Introductionmentioning
confidence: 99%
“…With these results, and as it was suggested in previous studies, the clinical course of AR might be altered in patients with impaired histamine metabolism [ 17 ]. There are many causes of malfunction or decrease in DAO activity [ 5 , 11 , 31 , 32 , 33 ] For example, carriers of DAO C2029G mutated allele tend to develop more severe symptoms of rhinitis and other histamine intolerance-related symptoms [ 17 , 18 , 34 ]. Therefore, in future studies this fact must be corroborated.…”
Section: Discussionmentioning
confidence: 99%